The Effectiveness of Global Sourcing in Malaysia: Risk Assessing in Construction Industry - Nurhaizan, Mohd Zainudin; Fadzida, Ismail; Lee, Chia Kuang; Noor Azlinna, Azizan (Universiti Malaysia Pahang, 2013)
Globalisation in general has laid the groundwork for change in companies in a way companies source and manufacture products. In fact, global sourcing is experiencing rebust growth around the world especially in OECD countries. This research paper intents to study current trends in Malaysia's construction industry for global sourcing and to establish the risks associated with global sourcing and their mitigation plans in order to determine the effectiveness of engaging global sourcing in construction industry in Malaysia. Through an intensive literature search, identification of construction trends in Malaysia relating to current situation and issues is carried out. From the allocated risks, a list of risk mitigation action and risks severity graphs are produced. Since this study specially concerns global sourcing in Malaysia, a pattern for Malaysia is then compared and analyzed with other countries in determining the effectiveness of global sourcing by using descriptive analysis. The outcome of this research shows that Malaysia exhibits lower level in terms of global sourcing risks as compared to other countries. This study significance for both international companies which favor Malaysia for global sourcing and the risks associated with global sourcing in Malaysia and its mitigation plans; simultaneously prepare both Malaysia to enter global arena and the international companies to have a global sourcing deal with Malaysia. For future research, so as to promote Malaysia to the notice internatioanl companies, a comparative study is conducted on the risk mitigation processes proposed by most international companies in order to ascertain whether or not the proposed risk mitigation suits Malaysia companies.